System quality and use of open educational resources among postgraduate students - Esan, Adedoyin Oluwatosin; Ogbomo, Monday Obaidjevwre; Ogbomo, Esoswo Francisca (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: OER is very beneficial and its adoption and usage by Nigeria universities as recommended by the federal government through National Universities Commission was expected to transmit to national acceptance because of the benefits accrued. Unfortunately, the story is different as so many universities are yet to key into this policy. Purpose: This study investigated the quality of the system and postgraduate students' use of open educational resources in federal universities in South-West, Nigeria. The purpose of the study was to find out how postgraduate students at federal universities in South-West Nigeria used open educational resources. Method: The study's research design is a correlational survey design and includes 9,436 master's degree students as its population; using quota sampling, the sample size is 377. 377 copies of the questionnaire were given in total, and 330 of those were determined to be usable, indicating an 88% response rate. With a criterion mean of 2.50, the data was analyzed using inferential statistics to address the research objectives. Findings: As a result, the following findings were reached. In South-West Nigerian federal universities, postgraduate students have access to excellent quality open educational resources. Postgraduate students use university-based free educational resources to a very little extent. The use of Open Educational Resources (OER) by postgraduate students at universities is negatively correlated with the quality of systems. Conclusion: The study thereby recommends that OER platform providers should ensure they sustain the system quality of OER repositories in order to attract more students to its usage and there should be training and retraining such as workshops to educate the postgraduate students on how to use OER.